The Sea as a Symbol of Spirituality in the Qur'an and the Bible: Julia Kristeva's Intertextual Approach: Laut sebagai Simbol Spiritualitas dalam Al-Qur’an dan Alkitab: Pendekatan Intertekstual Julia Kristeva - Riska Wahyuni; Ermaya Zunita Aprilia; Elok Atika; Muhammad Tubagus Soleh Tammimi Tammimi; Muhammad Ghifary Ramadhani Mallo (Takwil: Journal of Quran and Hadith Studies, 2025)
This study is grounded in the finding that the symbol of the sea in the Qur’an and the Bible reveals a parallel yet ambivalent structure of spiritual meaning, functioning both as a representation of humanity’s existential darkness and, simultaneously, as a manifestation of God’s greatness and omniscience. Based on this overarching finding, the study aims to examine the construction of the sea as a symbol in both sacred texts, to trace their similarities and differences through an intertextual lens, and to elucidate the symbolic relationship between the sea, humanity, and God within the two religious traditions. This research employs a qualitative, library-based methodology with a descriptive-analytical approach. Julia Kristeva’s intertextual theory is applied to compare narratives and representations of the sea in the Qur’an and the Bible, emphasizing the dialogical interaction between religious texts. The findings demonstrate that, despite emerging from distinct theological and historical contexts, both scriptures exhibit similar symbolic patterns in their interpretation of the sea. The sea is depicted as a space of inner darkness and moral disorder, as well as a sign of divine power that transcends human rationality. Consequently, this study contributes to the advancement of comparative religious discourse and broadens symbolic understanding in scriptural studies, particularly regarding the relationship between God, humanity, and nature.